The Computer Daybook: A Multifaceted Tool - Hawisher, Gail E. (English journal, 1988)
A computer daybook file allows teachers to monitor the progress of students learning to use word processors. Students are prompted to tell how they feel about working with the computers. Sample prompts are listed.